The nephrology crystal ball: the medium-term future - Zoccali, Carmine; Blankestijn, Peter J; Bruchfeld, Annette; Capasso, Giovambattista; Fliser, Danilo; Fouque, Denis; Goumenos, Dimitrios; Massy, Ziad; Rychlık, Ivan; Soler, Maria J; Stevens, Kate; Spasovski, Goce; et al. (Nephrology, dialysis, transplantation, 2020)
In January 2019, the ERA-EDTA surveyed nephrologists with questions on kidney care and kidney research designed to explore comprehension of the impact of alterations to organization of renal care and of advancements in technology and knowledge of kidney disease. Eight hundred and twenty-five ERA-EDTA members, ∼13% of the whole ERA-EDTA membership, replied to an ad hoc questionnaire. More than half of the respondents argued that kidney centres will be increasingly owned by large dialysis providers, nearly a quarter of respondents felt that many medical aspects of dialysis will be increasingly overseen by non-nephrologists and a quarter (24%) also believed that the care and long-term follow-up of kidney transplant patients will be increasingly under the responsibility of transplant physicians caring for patients with any organ transplant. Nearly half of the participants (45%, n = 367) use fully electronic clinical files integrating the clinical ward, the outpatient clinics, the haemodialysis and peritoneal dialysis units, as well as transplantation. Smartphone-based self-management programmes for the care of chronic kidney disease (CKD) patients are scarcely applied (only 11% of surveyed nephrologists), but a substantial proportion of respondents (74%) are eager to know more about the potential usefulness of these apps. Finally, European nephrologists expressed a cautious optimism about the application of omic sciences to nephrology and on wearable and implantable kidneys, but their expectations for the medium term are limited.
Keywords: Renal Dialysis; Kidney Transplantation; transplantation; nefrologové; Kidney Failure, Chronic; nefrologie; nephrology; private dialysis; transplantace ledvin; Humans; chronické selhání ledvin; dialýza ledvin; omic; lidé; future; Nephrology; Nephrologists